Pathological changes in the spleen in herbicide poisoning - Kakhkharov Navruzbek Ziyokulovich.; Nuritov Nurpullo Razhapovich. (Zien Journals, 2022)
The purpose of this work was to elucidate the structural foundations of the spleen in acute herbicide poisoning and to find ways to correct them with biocomplexes
Keywords: herbicide poisoning; spleen